An algorithm for bank operation of declining rate filters - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1998)
A mathematical theory and a computer algorithm for modeling variable declining rate filtration systems are presented. The use of harmonic mean conductivity in the calculation of laminar head loss through a filter medium is explained. It is mathematically proved that harmonic mean conductivity, as opposed to conductivity evaluated at average specific deposit, must be used if Darcy's law holds. The differences between the predictions based on the two approaches to calculating average hydraulic conductivity are demonstrated. The computer algorithm presented here is capable of predicting water level variations, effluent concentrations, individual filter velocities and productions as functions of rime. (C) 1998 Elsevier Science Ltd. All rights reserved.
Keywords: Darcy's law; declining rate filtration; filtration; water treatment; RATE FILTRATION